Generation of human iPSC-derived 3D bile duct within liver organoid by incorporating human iPSC-derived blood vessel - Erica Carolina; Yoshiki Kuse; Ayumu Okumura; Kenji Aoshima; Tomomi Tadokoro; Shinya Matsumoto; Eriko Kanai; Takashi Okumura; Toshiharu Kasai; S. Yamabe; Yuji Nishikawa; Kiyoshi Yamaguchi; et al. (2024)
In fetal development, tissue interaction such as the interplay between blood vessel (BV) and epithelial tissue is crucial for organogenesis. Here we recapitulate the spatial arrangement between liver epithelial tissue and the portal vein to observe the formation of intrahepatic bile ducts (BDs) from human induced pluripotent stem cells (hiPSC). We co-culture hiPSC-liver progenitors on the artificial BV consisting of immature smooth muscle cells and endothelial cells, both derived from hiPSCs. After 3 weeks, liver progenitors within hiPSC-BV-incorporated liver organoids (BVLO) differentiate to cholangiocytes and acquire epithelial characteristics, including intercellular junctions, microvilli on the apical membrane, and secretory functions. Furthermore, liver surface transplanted-BVLO temporarily attenuates cholestatic injury symptoms. Single cell RNA sequence analysis suggests that BD interact with the BV in BVLO through TGFβ and Notch pathways. Knocking out JAG1 in hiPSC-BV significantly attenuates bile duct formation, highlighting BVLO potential as a model for Alagille syndrome, a congenital biliary disease. Overall, we develop a novel 3D co-culture method that successfully establishes functional human BDs by emulating liver epithelial-BV interaction.